Dampak Pengumuman Pembagian Dividen Kas Terhadap Abnormal Return Pada Indeks LQ-45 - Kusno, John Iwan; Hartanto, Fransisca Tharia (Program Studi Akuntansi FPEB UPI, 2018)
The aim of this research is to examine the impact of cash dividend announcement to the abnormal return in the period before announcement, at the announcement, and after the announcement. The sample of this research is publicly listed companies in the LQ-45 index from 2015 to 2016. Market model is chosen to calculate the abnormal return. To test whether abnormal return is significant or not, we use t-test, one tailed test, at 5% significance level. Results of this research shows that Indonesian stock market is still not efficient since the abnormal return is significant at day two, day four, and day five after the cash dividend announceme